Alternating electric-field-induced assembly of binary mixtures of soft repulsive ionic microgel colloids - Jathavedan, Kiran; Bhat, Suresh K.; Mohanty, Priti S. (Journal of Colloid and Interface Science, 2019)
An external alternating electric field is used to study the assembly of a binary mixture of Poly(N-isopro pylacrylamide-co-acrylic acid) microgels in their swollen form at hydrodynamic size ratio 2:1 under deprotonated state. The AC field experiments were carried out at a fixed frequency of 100 kHz in the fluid regime for three number density ratios 1:3, 1:1 and 3:1 of big-to-small microgels using a confocal microscope. Strings with different types of co-assembly structures such as buckled, ring, flame and sandwich have been observed at low and intermediate field strengths at ratio 1:3, 1:1. In buckled and ring type, one or two small particles sit at the contact of two big particles and in the flame type, small particles arrange like a cone at end of the string. In the sandwich structure, several double small particle layers lie in between big particles. At high field strength, aggregation of strings and a phase separation into individual aggregates of strings from both big and small microgels have been observed. At higher ratio 3:1, the string formation is mostly dominated by big particles. Our experimental results are discussed with the recent simulation and experimental works on AC field induced structures in binary hard sphere mixtures. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: assembly; dipolar interactions; Microgels; Soft colloids